2005
DOI: 10.1016/s1808-8694(15)31285-4
|View full text |Cite
|
Sign up to set email alerts
|

Posture restrictions do not interfere in the results of canalith repositioning maneuver

Abstract: Post-maneuver restrictions do not influence the efficacy of Epley Maneuver for BPPV management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“… 25 Various studies showed short-term positive results after ORM performance in BPPV treatment. These studies had a follow-up variation between 72 hours and 6 weeks, 26 27 28 29 30 31 32 though there is no prognosis of a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Various studies showed short-term positive results after ORM performance in BPPV treatment. These studies had a follow-up variation between 72 hours and 6 weeks, 26 27 28 29 30 31 32 though there is no prognosis of a satisfactory outcome.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Cakir et al 17 added further controversy, because they concluded that postural restrictions and use of a cervical collar improved the effect of the CRM and that they should be recommended in the management of PSC BPPV. On the other hand, Casqueiro et al, 19 in 2008, and Fyrmpas et al, 30 in 2009, studying a total number of 463 patients, excluded postural restrictions from the management of BPPV.…”
Section: Synopsis Of Findingsmentioning
confidence: 99%
“…The results generated can serve as an important health indicator for elderly people and their caregivers. In addition, the system can offer recommendations on preferred sleep posture according to each elderly user's health condition [30]. For example, physicians generally suggest patients with coronary heart disease adopt a right-lateral sleep posture, and SPRS can alert the users whenever their sleep pattern is considered improper.…”
Section: • Posture Detectionmentioning
confidence: 99%